Effect of Cooperative Learning Strategy on Cognitive Activity of Students in Physics for Third Intermediate Grade Within schools of Basra Education - Ruqayah Abd Ali Qanbar (Genius Journals, 2023)
Physics is not in isolation from this development that the world is witnessing in development of teaching methods, as it is among the scientific subjects that are concerned with developing students' cognitive and mental capabilities and seeks to raise its level, so researchers have taken care of this subject and worked to embody this development by setting advanced concepts and research up level of education in the schools of Iraq and the Arab countries. The study aimed to know the effect of cooperative learning strategy in physics in the development of cognitive activity among students of the Third Mediterranean within the schools of Basra. Researcher adopted the semi - experimental curriculum to determine the impact of the independent variable on the dependent variable, relying on that experimental design with the two groups: the number of the research sample (32) students was divided into two volumes of an experimental group (16) students and a control group (16) students. Where they were chosen in a simple random manner from (Ahl al –Bayt ) Intermediate school in Basra Governorate, the morning government education for the third intermediate grade, and students were distributed in the control and experimental groups and distribution also within the same group, taking into account the differences in the characteristics of students, and the following study tools were applied to them: the illustrated intelligence test To check equal groups. Creative Thinking Test (Torrance) in its verbal form, and the statistical processing of data was done using: the average arithmetic, standard deviation, "T" test of two interconnected or two independent eyes, homogeneous and the most important of the condemnation: 1-There are statistical differences in the grades of the experimental group students between tribal and post measurement. 2-There are statistical differences between the grades of the control and experimental group in the post measurement
Keywords: Cooperative Learning Strategy; Cognitive Activity; Physics